SURGICAL TREATMENT OF PRESSURE ULCERS - Tudzarova Gjorgova, Smilja; Peev, Igor; Naceska, Andrijana (MACEDONIAN ASSOCIATION OF ANATOMISTS AND MORPHOLOGISTS, 2011)
Pressure sores or bedsores are injuries to the skin and underlying tissues that result from prolonged pressure on the skin. Bedsores most often develop on areas of skin that cover bony parts of the body, such as the heel, ankles, hips or buttocks. These wounds most often present themselves in immobilized or bedridden patients on parts of the body that are compressed between the skeleton and underlying surface. The treatment is often long lasting, time consuming and management is difficult process that demands enormous financial and human resources. The aim of this paper is to present our experience with the surgical treatment of the deep pressure sores. Our study presents a cohort of 30 patients that were surgically treated at the University Clinic for Plastic and Reconstructive Surgery, in Skopje, Republic of Macedonia, during a fifteen year period from 1996 to 2010. Emphasis of the surgical treatment was placed on harvesting and transplanting Cutaneous and Myofasciocutaneous flaps in order to cover the deep soft tissue defects. Results include statistical analyses of the group, systematization of the pressure ulcers according to the regions affected, utilized operative techniques as well as the average hospitalization stay. The youngest patient is a 10 years old child with a scalp pressure ulcer following a neurosurgery operation. The oldest patient is 83 years old male with a decubitus in the sacral region. Mean hospitalization stay is 26 days. Surgical treatment of the decubital ulcers, adequate and on time applied, in combination with appropriate pre- and post-operative care, gains satisfying functional and aesthetic results. That applies especially in selected patients where primary illness as reason for pressure ulcer is prone to successful rehabilitation.
Keywords: decubitus; reconstruction; flap